IRAS22150+6190: A POORLY STUDIED YOUNG STAR - Kuratov, K. S.; Zakhozhay, O. V.; Miroshnichenko, A. S.; Zakhozhay, V. A. (Одеські астрономічні публікації, 2016)
Many young stellar objects have been discovered in the course of the InfraRed Astronomical Satellite (IRAS) mission, which observed almost the entire sky in four photometric bands between 12 and 100 microns in 1989. These discoveries led to constraining the evolution of stars of various masses and the material that was left from the proto-stellar clouds. Investigation of young stars are important because they allow us to learn more about star and planet formation modes as well as better understand processes of the proto-stellar debris dispersal. Nevertheless, not all optical counterparts of such objects have been revealed or studied in detail. We report our multicolor optical photometric observations of IRAS 22150+6109 obtained at the Tien-Shan Astronomical Observatory near Almaty, Kazakhstan, as well as preliminary results of our analysis of the spectral energy distribution. Fundamental parameters of the star are estimated under an assumption that it has a zero-age main-sequence luminosity and a spectral type of B3. Our plans on further observations and modeling of the object are outlined.